Histori Fikih Islam: Faktor-Faktor Pertumbuhan, Kebekuan dan Reformasi - Muhammad Ikhsan; Azwar Iskandar (Islamadina : Jurnal Pemikiran Islam, 2022)
This research was conducted with the aim of: (1) knowing and analyzing the process of growing Islamic jurisprudence thought in the Islamic community; (2) knowing and analyzing the factors that caused the freeze of Islamic jurisprudence thought in the early era of its appearance; and (3) offer some reform efforts toward Islamic jurisprudence thought. This research uses library research method where library material is discussed and analyzed with content analysis techniques and descriptive analysis to support existing propositions and ideas from various references with historical approaches. The results showed that; (1) the growth of Islamic jurisprudence thought can grow in the midst of Islamic society due to the great need for the jurispruding laws themselves, where this need is higher with the emergence of various problems caused by differences in social and cultural conditions; (2) the freeze and cheese and the Islamic jurisprudence thought cannot be separated from several reasons, including excessive concern for the efforts of "infiltration" in Islamic jurisprudence and fanaticism of sects that go beyond the limits; and (3) reform efforts must begin by restoring the function and role of ijtihad as the main instrument of the development of Islamic jurisprudence that is carried out proportionately.